Routing metric and protocol for wireless mesh network based on information entropy theory - Turlykozhayeva, D.; Ussipov, N.; Baigaliyeva, A.; Temesheva, S.; Bolysbay, A.; Abrakhmatova, G.; Akhtanov, S. (Karaganda University named after academician E.A.Buketov, 2023)
In this work, the authors propose a routing algorithm based on information entropy theory for calculating the metric, considering the probability of packet loss. Information entropy theory serves as a robust foundation for evaluating uncertainty and disorder in data transmission, facilitating the development of a more resilient and intelligent routing strategy. In contrast to existing algorithms, the proposed approach enables a more accurate assessment of data transmission quality within the network, optimizing the routing process for maximum efficiency. The experimental results demonstrate a significant enhancement in network service quality while maintaining high performance. To validate the algorithm's effectiveness, a series of experiments were conducted, evaluating key performance metrics such as throughput, delay, and packet loss. A comparative analysis with established routing algorithms was also carried out, allowing for the assessment of advantages and drawbacks in relation to well-known algorithms. The findings suggest that the proposed algorithm surpasses traditional routing methods in optimizing data transmission quality and overall network efficiency.
Keywords: Routing; entropy; information; wireless mesh network